Fyrverkerier och dess påverkan på den domesticerade hunden (Canis lupus familiaris) : hur påverkas hundens välfärd? - Höglin, Amanda (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
Fireworks are low explosive pyrotechnics that are frequently used around the world during holidays such as New Year´s. Even though fireworks are entertaining to a lot of people, they are not fun for everyone. Among those last named you can find the dog (Canis lupus familiaris). This review shows that pyrotechnics are a reason to possible decreased welfare in dogs. Fireworks affect dogs in both behavioural and physiological ways. Excessive licking, hyperactivity, raised cortisol -levels and heart rates are a few of those. Both dogs and owners are shown to suffer a great deal of stress from fireworks, dogs because they are scared and owners because they do not know how to protect and help their dogs. Owners should therefore be encouraged to seek help if they suspect their dog to suffer during firework events. The sound of fireworks can also cause dogs to suffer from other closely related stimuli such as thunderstorms or gunshots. It is therefore important that owners seek help if their dogs are sensitive to noise in general. Pheromones, medication, pressure vests and behavioral treatment programs have all been tested as possible remedies for this problem. Unfortunately, this review also shows that neither of these works for all individuals suffering from fear of fireworks. In view of the findings in this study, legislation should regulate the decrease of fireworks use. It is well on its way where several local authorities in Sweden has both decreased the use of pyrotechnics and regulated the use of it in their local regulations. It is partly regulated in such a way that specific timeframes determine when fireworks are legal to use.